Deep-sea Entoprocta from the Sea of Okhotsk and the adjacent open Pacific abyssal area: New species and new taxa of host animals. (August 2018) - Borisanova, Anastasia O.; Chernyshev, Alexei V.; Ekimova, Irina A.
Abstract: The Entoprocta fauna still remains almost unexplored: many geographical areas have not yet been studied for their diversity, and almost nothing is known about deep-sea species. We described four new species of solitary Entoprocta from the family Loxosomatidae. The material was collected within a depth range between 3206 m and 3580 m during the German-Russian deep-sea expedition SokhoBio aboard R/V Akademik Lavrentyev in July - August 2015 in the Kuril Basin of the Sea of Okhotsk, Bussol Strait, and the adjacent open Pacific abyssal area. We used methods of light and scanning electronic microscopy and also laser confocal microscopy for morphological studies. Maximum likelihood and Bayesian analyses of partial DNA sequences of 18S and 28S rRNA genes were used to reconstruct phylogenetic trees. Loxosomella aeropsis sp. nov. was found on spines of the sea urchin Aeropsis fulva ; Loxosomella cyatiformis sp. nov. was found on shells of the propeamussiid bivalve Catillopecten squamiformis ; Loxosomella malakhovi sp. nov. was found living as an epibiont of the nephtyid polychaete Aglaophamus sp., and Loxosomella sextentaculata sp. nov., as an epibiont of the spionid polychaete Laonice sp. Echinoidea and Bivalvia have been first recorded as hosts of loxosomatid entoprocts in their symbiotic associations. A molecular phylogenetic analysis of partial 18S rRNA and 28S rRNA of Loxosomella aeropsis sp. nov., L . cyatiformis sp. nov., and L . malakhovi sp. nov. show that these species nest in the clade of solitary entoprocts among other Loxosomella species. Musculature of investigated species, Loxosomella aeropsis sp. nov and L . malakhovi sp. nov., is typical for loxosomatids and includes the longitudinal muscles of a stalk, the musculature of the digestive tract, the atrial muscular ring, and tentacle muscles. Each species has species-specific muscles so details of myoanatomy can be used for identification of species in addition to other morphological features.